2014
DOI: 10.1590/1414-431x20133277
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent quantitative PCR of Mycobacterium tuberculosis for differentiating intestinal tuberculosis from Crohn's disease

Abstract: Intestinal tuberculosis (ITB) and Crohn's disease (CD) are granulomatous disorders with similar clinical manifestations and pathological features that are often difficult to differentiate. This study evaluated the value of fluorescent quantitative polymerase chain reaction (FQ-PCR) for Mycobacterium tuberculosis (MTB) in fecal samples and biopsy specimens to differentiate ITB from CD. From June 2010 to March 2013, 86 consecutive patients (38 females and 48 males, median age 31.3 years) with provisional diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Therefore, a total of only nine articles were eligible for further analysis. [ 4 14 15 21 22 23 24 25 26 ] The study selection process is shown in Figure 1 , and the basic characteristics of the selected studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a total of only nine articles were eligible for further analysis. [ 4 14 15 21 22 23 24 25 26 ] The study selection process is shown in Figure 1 , and the basic characteristics of the selected studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in the literature, there are limited data on the use of fecal samples for detecting MTB DNA to distinguish ITB from CD. Two eligible articles using fecal samples[ 4 21 ] reported sensitivities of 0.83 and 0.79 and respective specificities of 0.92 and 0.89. In addition, Balamurugan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that used fecal samples reported TB PCR results positive for IS6110 sequence in 79% of ITB patients and in 5% of CD patients, and concluded that fecal TB PCR combined with TB culture of mucosa biopsy specimen was a good test to distinguish the two diseases [26]. The fluorescent quantitative TB PCR using fecal samples had greater sensitivity than that using tissue samples [27].…”
Section: Discussionmentioning
confidence: 99%
“…This differentiation is also increasingly a problem in countries where ITB is not common, but rapidly growing immigrant populations from areas of high ITB prevalence make ITB an important diagnostic possibility. A definite diagnosis of ITB depends on methods that have unsatisfactorily low sensitivities, including 5.3–37.5% for acid-fast bacilli tissue staining (1–3), 23–46% for mycobacterial culture (4,5), and 36.4–67.9% for PCR (3,4,68). Therefore, ITB still cannot be confidently excluded even when all the above results are negative, thus the current Asia-Pacific guidelines recommend 8–12 weeks of empirical antituberculosis treatment for patients with diagnostic uncertainty, owing to the potentially fatal complications if immunosuppressive agents are wrongly prescribed to ITB patients (9).…”
Section: Introductionmentioning
confidence: 99%